A Legal Analysis of the Implementation of Inpatient Care Based on BPJS Hospital Class Standards - Q.Situmorang; R.Pane (International Medical Journal Corp. Ltd, 2026)
Introduction: The shifting paradigm of public healthcare in Indonesia, driven by the Social Security Administrator for Health (BPJS Kesehatan), mandates a standardized approach to inpatient services. This study legally analyzes the transition from traditional care classes to a unified criteria system. Methods: This research employs a normative legal method (doctrinal legal research), examining primary statutory regulations and secondary legal authorities regarding healthcare services. Results: The findings reveal that while the standardization of inpatient classes aims to fulfill the constitutional right to health equity, significant legal ambiguities remain concerning regulatory compliance, infrastructural readiness, and implementation uniformities among tier-one to tier-three hospitals. Discussion: The discussion delves deeply into the divergence between regulatory ideals and the socio-legal reality of healthcare facilities. It provides a comprehensive literature review on the right to health, evaluating the operational bottlenecks, institutional resistance, and contractual dynamics between BPJS and healthcare providers under the lens of administrative law. Conclusions: In conclusion, the standardization mechanism requires synchronous harmonized legislation and explicit enforcement clauses to prevent standard degradation. It is recommended that the government issue stricter technical guidelines and establish a collaborative oversight committee to bridge the current regulatory and infrastructural gaps.